An autoclave-free ultra-high performance extruded cement fiber board and a preparation method thereof

CN122977795APending Publication Date: 2026-10-27GUANGXI SUPER POLYMER TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611473345.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0009]针对传统挤出水泥纤维板强度低、必须蒸压养护、脱模周期长、高掺纤维素醚抑制水化、单纤维增韧脆性大、现有UHPC无法适配挤出成型等技术缺陷,本发明提供一种免蒸压超高性能挤出水泥纤维板及其制备方法,通过多级密堆骨料级配、复合胶凝常温激发、多尺度三元复合纤维、五元流变调控四大核心体系的协同配合,在极低纤维素醚掺量下实现稳定连续挤出,全程常温养护无需蒸压釜,短时间内即可快速脱模,成品具备高力学强度、高韧性、低吸水率与高耐久性能,适配多种应用场景

Benefits of technology

[0035]1.常温免蒸压养护体系,实现低碳生产与产线高适配性

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977795A_ABST
    Figure CN122977795A_ABST
Patent Text Reader

Abstract

The application discloses an autoclave-free super high-performance extruded cement fiber board and a preparation method thereof, and belongs to the field of inorganic high-performance cementitious composite materials. The board is prepared by using 52.5 ordinary portland cement as a reference, through multistage dense aggregate grading, composite cement activation at room temperature, synergistic effect of multiscale ternary composite fibers and a five-element rheological regulation system, precise bin allocation, segmented high-speed stirring, vacuum extrusion molding, room temperature standing pre-curing, rapid demolding, room temperature natural curing and cutting finishing, and the whole process does not need autoclave curing, the cellulose ether content is extremely low, the finished product can be demolded in 2-4 hours, has excellent mechanical properties and a dense and durable matrix, and can be widely applied to high requirement scenes such as fabricated load-bearing components, sound barriers, explosion-proof protection and the like, and has low production energy consumption, strong production line adaptability, and remarkable economic and environmental protection benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of inorganic high-performance cementitious composite materials, specifically relating to an autoclaved-free ultra-high performance extruded cement fiberboard and its preparation method. Background Technology

[0002] Extrusion cement fiberboard (ECP) is a widely used inorganic board material in the field of prefabricated buildings. Leveraging the advantages of continuous vacuum extrusion molding, it can produce thin-plate components with relatively dense matrix and high dimensional accuracy, making it widely applicable in non-load-bearing building scenarios such as exterior wall decoration, interior ceilings, and partition walls. After decades of industrial development, the mainstream ECP production technologies in the industry are currently divided into two categories: the traditional high-temperature, high-pressure autoclaving route and the low-temperature, autoclaving-free conventional curing route. Both routes have their own technical limitations and performance shortcomings.

[0003] In existing industrial-scale autoclaved aerated concrete (ECP) technologies, typical production processes employ high dosages of cellulose ether thickeners to regulate the rheological properties of the mixture, meeting the lubrication and water retention requirements of continuous vacuum extrusion molding. After molding, the green body is placed in an autoclave for prolonged curing under high temperature and pressure saturated steam. This high-temperature and high-pressure condition activates the pozzolanic activity of mineral admixtures such as silica fume and fly ash, enabling the slab to achieve basic mechanical strength. While this process is relatively mature, it suffers from inherent limitations such as high energy consumption, large equipment investment, and long production cycles. Furthermore, the high dosage of cellulose ethers inhibits the cement hydration process, restricting production efficiency and affecting the final mechanical properties of the slab.

[0004] Furthermore, some autoclaved extruded fiber cement products rely solely on a single fiber type in their reinforcement system, failing to construct a multi-scale fiber synergistic toughening network. This results in boards with relatively insufficient mechanical and durability properties, low flexural strength, and significant material brittleness. Their applications are limited to non-load-bearing or composite structural substrates, making it difficult to meet the structural requirements of higher load levels.

[0005] Patent application CN120794553A discloses an extruded carbonized fiber cement board and its preparation method. It proposes using a calcium silicate mineral phase (such as γ-C2S) with high carbonization activity and low hydration activity to replace traditional cement. This phase, combined with fibers and plasticizers, is vacuum extruded and then cured in a CO2 atmosphere at room temperature (20~40℃) and slightly higher atmospheric pressure (0.1~0.3MPa). The carbonization reaction generates calcite, providing strength. This method avoids the problem of decreased plasticity caused by cement hydration, and the energy consumption of CO2 curing is significantly lower than that of traditional autoclaving. However, it requires a corresponding CO2 supply and a closed curing environment, and the carbonization time (2~48h) places certain requirements on the process organization.

[0006] In addition to the aforementioned technical solutions, current conventional non-autoclaved cement fiberboard in the industry generally adopts the method of lowering the curing temperature to avoid the high investment in autoclaving equipment. However, it does not systematically optimize the cementitious system, particle size distribution, fiber reinforcement system, and admixture system. It only ensures basic performance by increasing the cement content and the amount of cellulose ether, resulting in low strength, poor impact resistance, high water absorption, and insufficient durability of the finished product. It can only be used for simple interior decorative panels and cannot be applied to scenarios with high load and high durability requirements. At the same time, most of the currently disclosed ultra-high performance concrete (UHPC) formulations are suitable for casting and compression molding processes. The high viscosity of the mixture and the rheological properties cannot meet the production requirements of continuous extrusion equipment. Moreover, most UHPC technical solutions still rely on autoclaving or steam curing to assist hydration, which cannot be directly adapted to the mass production needs of existing ECP extrusion production lines.

[0007] The common defects of existing technologies can be summarized in five aspects: First, they require autoclave equipment, which results in high energy consumption, large equipment investment, and high carbon emissions, which does not conform to the development direction of green and low-carbon industries. Second, high cellulose ether content severely inhibits cement hydration, resulting in long demolding cycles, low pallet turnover efficiency, and permanent reduction in the final strength of the board and increased water absorption. Third, the toughening effect of single-component fiber-reinforced systems is limited, and they cannot inhibit the propagation of multi-scale cracks, resulting in brittle boards with poor impact resistance. Fourth, the aggregate gradation design is coarse, lacking multi-level particle gradient filling, resulting in high matrix porosity and insufficient durability. Fifth, existing UHPC technology is incompatible with extrusion processes, making it impossible to achieve mass production of ultra-high performance boards on existing ECP production lines.

[0008] To address the common challenges in the industry, the development of an ultra-high performance cement fiberboard technology that is autoclaved-free throughout the entire process, has low cellulose ether content, multi-scale fiber toughening, excellent mechanical properties, and is compatible with existing extrusion production lines has significant industrial value and technological significance. Summary of the Invention

[0009] To address the shortcomings of traditional extruded cement fiberboard, such as low strength, the need for autoclaving, long demolding cycles, high cellulose ether content inhibiting hydration, high toughness and brittleness of single fibers, and the inability of existing UHPC to adapt to extrusion molding, this invention provides an autoclaved-free ultra-high performance extruded cement fiberboard and its preparation method. Through the synergistic cooperation of four core systems—multi-stage close-packed aggregate gradation, room-temperature activation of composite cementitious materials, multi-scale ternary composite fibers, and pentaneous rheological control—stable and continuous extrusion is achieved with extremely low cellulose ether content. The entire process requires room-temperature curing without an autoclave, and demolding can be completed quickly in a short time. The finished product has high mechanical strength, high toughness, low water absorption, and high durability, making it suitable for various application scenarios.

[0010] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0011] An autoclaved aerated ultra-high performance extruded cement fiberboard, based on 100 parts by weight of 52.5 ordinary Portland cement, comprises the following components:

[0012] Cementitious components: 15-25 parts silica fume, 10-20 parts Class I fly ash, 5-10 parts calcium silicate;

[0013] Aggregate composition: 50-70 parts of 40-60 mesh quartz sand, 30-50 parts of 80-100 mesh quartz sand, and 20-30 parts of 400 mesh quartz powder;

[0014] Reinforcing fibers: 20-40 parts of copper-plated steel fiber with a length of 12-15mm, 2-4 parts of basalt fiber with a length of 6-9mm, and 2-3 parts of coniferous wood fiber;

[0015] Chemical admixtures: 1.0-2.0 parts of powdered polycarboxylate superplasticizer, 0.1-0.3 parts of cellulose ether, 6-12 parts of organic-inorganic hybrid modified styrene-acrylic polymer emulsion with 50% solid content, 0.5-1.5 parts of calcium formate, and 0.03-0.08 parts of sodium gluconate;

[0016] Mixing medium: 20-25 parts water;

[0017] The cement fiberboard is produced by vacuum extrusion molding and natural curing at room temperature, without any autoclaving process.

[0018] Furthermore, the viscosity of the cellulose ether is 20,000~40,000 mPa·s; the calcium silicate is γ-type dicalcium silicate micro powder with a specific surface area ≥450 m². 2 / kg.

[0019] Furthermore, the organic-inorganic hybrid modified styrene-acrylic polymer emulsion is prepared by seed emulsion polymerization of butyl acrylate, methyl methacrylate, styrene, γ-methacryloyloxypropyltrimethoxysilane, and acidic nano silica sol.

[0020] Further, by mass percentage, the raw materials of the organic-inorganic hybrid modified styrene-acrylic polymer emulsion include: 25-30% butyl acrylate, 15-20% methyl methacrylate, 12-18% styrene, 3-6% γ-methacryloyloxypropyltrimethoxysilane, 8-12% acidic nano silica sol with a solid content of 30%, 2-4% polyvinyl alcohol, 1.5-2.5% sodium dodecyl sulfate, 1.0-2.0% nonylphenol polyoxyethylene ether, 0.3-0.8% ammonium persulfate, 0.2-0.5% sodium bicarbonate, and the balance being deionized water.

[0021] Furthermore, the total water-cement ratio of the cement fiberboard is 0.17~0.20, and the total water includes the mixing water and the water introduced by the organic-inorganic hybrid modified styrene-acrylic polymer emulsion.

[0022] like Figure 1 A method for preparing autoclaved aerated concrete (AAC) ultra-high performance extruded cement fiberboard includes the following steps:

[0023] (1) Precise compartmentalization and batching: Weigh each powder raw material, reinforcing fiber, chemical additives and mixing water according to the ratio, store them in separate compartments and measure them independently;

[0024] (2) Segmented high-speed mixing: First, dry mix the powder raw materials evenly, then add the reinforcing fiber and dry mix to disperse, and finally add the mixing water and organic-inorganic hybrid modified styrene-acrylic polymer emulsion for wet mixing to obtain plastic mixture;

[0025] (3) Vacuum extrusion molding: The mixture is fed into a vacuum extruder and continuously extruded under negative pressure to obtain a billet;

[0026] (4) Pre-curing at room temperature: Place the billet in a room temperature environment for pre-curing;

[0027] (5) Rapid demolding: Demolding is performed after the compressive strength of the blank reaches the demolding strength;

[0028] (6) Natural curing at room temperature: After demolding, the boards are cured at room temperature until the target age.

[0029] (7) Cutting and finishing: The finished product is obtained by cutting the cured board to a fixed length and sealing the edges.

[0030] Furthermore, in step (2), the blade linear velocity of the dry mixing is 2.5~3.5m / s, the dry mixing time of the powder is 3~5min; the reinforcing fiber is added in batches, the total dry mixing time is 4~7min; and the wet mixing time is 4~6min.

[0031] Furthermore, in step (3), the extruder vacuum degree is -0.06~-0.09MPa, the extrusion speed is 0.8~1.5m / min, the screw speed is 18~28r / min, and the die pressure is 1.0~1.4MPa.

[0032] Furthermore, in steps (4) and (5), the pre-curing environment temperature is 20±5℃, the relative humidity is 60~70%, the pre-curing time is 2~4h, and the demolding strength threshold is ≥12MPa.

[0033] Furthermore, in step (6), the ambient temperature for natural curing is 20±5℃, the relative humidity is 60~70%, and the curing period is not less than 28 days.

[0034] Compared with the prior art, the technical advantages of the present invention are as follows:

[0035] 1. A room-temperature, autoclaving-free curing system enables low-carbon production and high adaptability to production lines.

[0036] This invention, through the systematic design of the material system, eliminates the autoclaving process necessary for traditional ECP production, thus freeing it from dependence on high-pressure equipment such as autoclaves. The composite cementitious room-temperature activation system constructed in this invention, combined with the long-term internal curing effect of calcium silicate, can continuously drive the pozzolanic reaction of silica fume and fly ash at room temperature and pressure, generating sufficient high-density hydration products to ensure the strength and density of the board. Eliminating the autoclaving process eliminates the need for autoclaves, steam boilers, and other equipment in the production line, significantly reducing fixed asset investment, making it particularly suitable for upgrading production lines of small and medium-sized enterprises. Existing traditional extruded cement fiberboard production lines do not require replacement of the core main unit; only adjustments to the batching and mixing parameters are needed for rapid conversion, resulting in low modification costs and strong adaptability. Simultaneously, the autoclaving-free process significantly reduces energy consumption and carbon emissions, aligning with the development direction of green building materials and low-carbon industries, helping enterprises meet environmental policy requirements, obtain green building material certifications, and enhance product market competitiveness.

[0037] 2. A composite rheology control system to resolve the industry contradiction between extrusion performance and hydration intensity.

[0038] This invention constructs a five-element composite rheology control system composed of polycarboxylate superplasticizer, organic-inorganic hybrid modified styrene-acrylic polymer emulsion, trace amounts of cellulose ether, calcium formate, and sodium gluconate, fundamentally resolving the long-standing technical contradiction in the extruded cement fiberboard industry of "the incompatibility between extrusion performance and hydration strength." In this system, powdered polycarboxylate superplasticizer ensures uniform particle dispersion at ultra-low water-cement ratios, providing basic fluidity; the organic-inorganic hybrid modified styrene-acrylic polymer emulsion forms a flexible lubricating film between the material and the die during extrusion, undertaking the main lubrication function and ensuring continuous and stable extrusion and the surface quality of the green body; the trace amounts of cellulose ether only provide short-term surface water retention, and their extremely low dosage does not easily hinder the migration of hydrated ions, effectively eliminating the inhibitory effect of cellulose ether on cement hydration; calcium formate regulates the early hydration process of cement, accelerating early strength development and shortening the demolding cycle; sodium gluconate adjusts the setting time of the mixture, reasonably extending the extrusion operating window and preventing premature solidification and blockage of the material in the barrel. The five components each perform their respective functions and work synergistically to achieve the desired effect without relying on high levels of cellulose ether (the amount of cellulose ether used in this invention is compared to that used in traditional ECP). Figure 2 As shown in the figure, it achieves excellent extrusion rheological properties and molding quality, while ensuring the normal and orderly progress of the hydration reaction, thus achieving a simultaneous improvement in processing performance and mechanical strength.

[0039] 3. A three-level fiber synergistic toughening system constructs a full-scale crack-resistant network to achieve pseudo-ductile damage.

[0040] This invention employs a three-tiered composite reinforcement system constructed from copper-plated steel fibers, basalt fibers, and coniferous wood fibers. The three fibers function at the macroscopic, mesoscopic, and microscopic levels, forming a graded crack-prevention network covering the entire scale. Copper-plated steel fibers bear macroscopic tensile stress, bridging macroscopic crack propagation and absorbing fracture energy, significantly improving flexural and impact resistance. Basalt fibers, distributed in the interfacial transition zone, inhibit microcrack initiation, reduce initial defects, and improve interfacial adhesion and matrix homogeneity. Coniferous wood fibers optimize the plasticity and water retention of the mixture, enhancing the plasticity and shape retention of the green body and inhibiting surface shrinkage cracks. The three fibers work synergistically to induce pseudo-ductile failure characteristics in the board's failure process, altering the traditional instantaneous brittle fracture mode of boards and significantly improving the structural safety, disaster resistance, and reliability of the board.

[0041] 4. Synergistic effect of multi-level particle packing and composite cementitious activation to achieve extreme densification of the matrix and a leap in durability.

[0042] This invention employs a refined particle size distribution design based on the closest packing theory. Through a gradient combination of coarse, medium, and fine quartz aggregates with micro / nano components, a continuous particle size distribution from millimeter to nanometer scale is constructed, significantly reducing the system's porosity. The hydration products of the composite cementitious system continuously fill micropores and interfacial defects, ultimately forming an extremely dense, homogeneous matrix structure. This structure endows the board with extremely low water absorption and excellent impermeability, freeze-thaw resistance, and corrosion resistance. External moisture and corrosive media have difficulty penetrating the matrix, effectively inhibiting freeze-thaw damage and acid / alkali corrosion. The board can serve stably for extended periods in complex outdoor natural environments and industrial corrosive conditions, significantly extending its service life compared to traditional ECP boards, thus expanding the product's application scenarios and life-cycle value.

[0043] 5. Early-stage rapid development mechanism to adapt to continuous production and improve capacity efficiency.

[0044] This invention achieves rapid early strength development of the preform through the synergistic effect of multiple mechanisms, significantly shortening the demolding cycle. Ultra-low cellulose ether eliminates the hindrance to the hydration reaction, calcium formate accelerates the hydration process of tricalcium silicate, and the organic-inorganic hybrid modified styrene-acrylic polymer emulsion, after film formation, intertwines with the initial hydration products to form an early composite skeleton. This triple effect enables the preform to rapidly reach the demolding strength threshold at room temperature, significantly shortening the demolding cycle compared to traditional processes. Rapid demolding significantly improves the turnover efficiency of production pallets, resulting in a substantial increase in sheet production per unit time with the same factory area and equipment configuration, effectively reducing fixed asset depreciation and labor management costs. Simultaneously, the entire process of natural curing at room temperature eliminates the waiting period of the autoclaving process, making the production flow highly compatible with continuous extrusion processes. The overall production rhythm is smoother and more continuous, significantly improving the capacity utilization rate and overall economic benefits of the production line.

[0045] Technical principle of the invention:

[0046] 1. Synergistic mechanism of multi-level particle dense packing

[0047] 40-60 mesh coarse quartz sand forms a rigid main framework, providing primary structural support and defining the volumetric framework. 80-100 mesh medium quartz sand fills the voids between coarse aggregates, reducing void volume, lowering internal friction resistance, and improving extrusion flowability. 400 mesh quartz powder fills the micron-sized pores between medium aggregates and cementitious particles, increasing packing density. Silica fume nanoparticles embed into the gaps between ultrafine fillers and cementitious particles, achieving nanoscale filling, while their high activity provides ample reaction sites for subsequent hydration reactions. Fly ash microspheres act as lubricants due to the ball-bearing effect, improving flowability and extrusion processability. Calcium silicate particles fill micro- and nano-pores, serving as nucleation sites for CSH gel, slowly releasing water of crystallization to form long-lasting internal curing.

[0048] The particles of each grade form a continuous gradient from large to small in size, and are nested and filled in layers to achieve the densest packing, minimize the porosity, reduce the amount of hydration products required for filling, improve the initial density, reduce the consumption of cementitious materials, and provide a solid particle gradation basis for high-performance matrices under ultra-low water-cement ratio.

[0049] 2. Synergistic mechanism of composite gelation activated at room temperature

[0050] When silicate cement comes into contact with water, it undergoes a rapid hydration reaction, generating initial CSH and Ca(OH)2, which provide early strength through setting and hardening.

[0051] Calcium silicate continuously dissolves Ca in the system 2+ With OH - Maintaining a highly alkaline environment in the system provides the pozzolanic reaction conditions for the active SiO2 and Al2O3 in silica fume and fly ash. The active silica-alumina components undergo a secondary reaction with Ca(OH)2 at high alkalinity and room temperature, generating a high-density CSH gel with a low calcium-to-silicon ratio and hydrated calcium aluminate. This fills micropores and interfacial transition zones, improving matrix density, optimizing interfacial structure, and enhancing the interfacial bonding strength between aggregates, fibers, and the matrix. Simultaneously, the calcium silicate crystal water is slowly released during the hydration process, forming a long-lasting internal curing effect, providing continuous moisture to the low water-to-binder ratio system, and ensuring the full progress of the pozzolanic reaction.

[0052] The entire composite cementitious system, through the combination of early strength activation and long-lasting alkali activation, can achieve full reaction of mineral admixtures and continuous strength growth without the need for external high temperature and high pressure, thus replacing the activation effect of traditional autoclaving.

[0053] 3. Three-scale fiber-grade crack-resistant toughening mechanism

[0054] Copper-plated steel fibers (12-15mm) act as a macroscopic reinforcing phase, bridging tensile stress across cracks and improving flexural and impact resistance. Basalt fibers (6-9mm) are distributed in the interfacial transition zone, pinning and inhibiting microcrack initiation and propagation, improving interfacial adhesion and matrix homogeneity, and optimizing stress distribution. Coniferous wood fibers enhance the plasticity and cohesion of the mixture, improve the plasticity and shape retention of the extruded preform, inhibit drying shrinkage stress concentration, and reduce surface microcracks. Figure 3 As shown, the three types of fibers form a full-scale crack-resistant network spanning from nanometers to micrometers to macrometers. The entire failure process is gradual and continuous, exhibiting pseudo-ductility characteristics with a slow decrease in load, which significantly improves structural safety and reliability.

[0055] 4. Synergistic Mechanism of Five-Element Rheological Regulation

[0056] Powdered polycarboxylate superplasticizer is adsorbed onto the surface of cementitious and aggregate particles. It breaks up agglomeration through electrostatic repulsion and steric hindrance, so that the particles are evenly dispersed. It provides basic fluidity at ultra-low water-cement ratio and ensures uniform distribution of each component.

[0057] Organic-inorganic hybrid modified styrene-acrylic polymer emulsion is the core functional component of the rheology control system. During extrusion molding, emulsion particles accumulate on the inner wall of the die, forming a continuous organic-inorganic composite flexible lubricating film between the material and the die wall. This significantly reduces frictional resistance, ensuring continuous and stable extrusion while preventing molding defects such as delamination, stringing, and edge defects in the preform. After dehydration and film formation, the polymer-nanosilicon hybrid network bridges microcracks, absorbs fracture energy, and improves matrix toughness. Simultaneously, the siloxane groups in the emulsion hydrolyze and chemically bond with cement hydration products, strengthening the organic-inorganic interface, overcoming the traditional problem of weak interfaces, and simultaneously improving mechanical and durability properties.

[0058] Cellulose ethers primarily function to retain surface moisture for short periods, slowing down the initial evaporation rate of surface moisture and preventing micro-cracks caused by drying shrinkage in the green body. Due to their extremely low dosage, cellulose ethers cannot form a continuous coating layer on the surface of cementitious particles and do not block the migration of hydrated ions. Therefore, they do not significantly inhibit the cement hydration reaction, thus avoiding the side effects of traditional high-dosage cellulose ethers at their source.

[0059] Calcium formate, as an early strength agent, can accelerate the hydration of tricalcium silicate in the early stage of the hydration reaction, promote the formation of early products, accelerate strength development, and shorten demolding time.

[0060] Sodium gluconate, as a retarding component, adsorbs onto the surface of cement particles, delaying the induction period of the hydration reaction, adjusting the setting time of the mixture, and reasonably extending the extrusion operation window. This prevents the material from solidifying prematurely in the extruder barrel, thus avoiding mold blockage and ensuring safe continuous production.

[0061] 5. Mechanism of action of organic-inorganic hybrid modified styrene-acrylic polymer emulsion

[0062] Butyl acrylate (BA) is a soft monomer that provides flexibility to polymer chain segments, enabling the emulsion film to have good elasticity and elongation, adapt to the micro-deformation of the cement matrix, and prevent the film layer from cracking and falling off.

[0063] Methyl methacrylate (MMA) is a hard monomer that provides polymer strength and glass transition temperature, improving the hardness, abrasion resistance, and scratch resistance of emulsion films.

[0064] Styrene (St) is a hard monomer. Introducing a benzene ring structure improves the polymer's water resistance, alkali resistance, and UV aging resistance, while reducing emulsion costs.

[0065] γ-Methacryloxypropyltrimethoxysilane (KH-570) is an organosiloxane coupling agent. The two ends of the molecule contain polymerizable double bonds and hydrolyzable siloxane groups, respectively. The double bonds participate in free radical polymerization and are grafted onto the polymer chain. After hydrolysis, the siloxane groups form Si-O-Si chemical bonds with nano-silica and cement hydration products, realizing molecular-level bonding between the organic and inorganic phases.

[0066] Acidic nano-silica sol is an inorganic nano-reinforcing phase that is uniformly dispersed inside and on the surface of emulsion particles, forming an organic-inorganic hybrid structure. This improves the hardness, modulus, water resistance, and weather resistance of the emulsion film, while also providing crystal nuclei for cement hydration and promoting the growth of hydration products in the interfacial region.

[0067] Polyvinyl alcohol (PVA) can protect colloids by adsorbing onto the surface of emulsion particles to form a steric stabilizing layer, preventing the emulsion particles from agglomerating and settling, and improving the storage and mechanical stability of the emulsion.

[0068] Sodium dodecyl sulfate (SDS) is an anionic emulsifier that reduces the interfacial tension between oil and water, provides electrostatic repulsion to stabilize emulsion particles, and forms a composite emulsion system when combined with nonionic emulsifiers.

[0069] Nonylphenol polyoxyethylene ether (OP-10) is a nonionic emulsifier that stabilizes the emulsion through steric hindrance and works synergistically with anionic emulsifiers to improve the electrolyte stability and freeze-thaw stability of the emulsion.

[0070] Ammonium persulfate (APS) is a thermal initiator. When heated, it decomposes to generate free radicals that initiate monomer polymerization, thus controlling the polymerization rate and molecular weight distribution.

[0071] Sodium bicarbonate (NaHCO3) is a pH buffer that adjusts the pH of the polymerization system to a weakly alkaline range, ensuring a stable decomposition rate of the initiator and preventing emulsion rancidity.

[0072] Synergistic effect mechanism: ① Soft and hard monomers are synergistically regulated to control the glass transition temperature through optimized ratio. BA provides flexibility, while MMA and St provide strength and weather resistance. The optimized ratio of the three ensures that the emulsion film has both good elasticity and hardness after film formation, adapting to the deformation and stress requirements of the cement matrix; ② Anionic and nonionic emulsifiers provide synergistic stabilization. SDS provides electrostatic stability, and OP-10 provides steric hindrance stability. The combination of the two gives the emulsion excellent electrolyte stability and mechanical stability, adapting to the high ionic strength environment of cement paste; ③ KH-570 and acidic nano silica Synergistic hybridization: KH-570 acts as a molecular bridge connecting organic polymers and inorganic nanoparticles, forming a chemically bonded hybrid structure; ④ PVA protective colloid and emulsifiers (SDS, OP-10) work synergistically to further enhance the mechanical and storage stability of the emulsion, adapting to high-speed stirring and extrusion shearing conditions; ⑤ APS and NaHCO3 synergistically regulate the polymerization rate: APS provides a stable source of free radicals, and NaHCO3 maintains the pH stability of the system. The combination of the two makes the polymerization reaction stable and controllable, and the performance deviation between batches of emulsion is controlled within 5%.

[0073] Using seed polymerization as its core, precise control of core-shell structure and particle size distribution is achieved by regulating polymerization temperature, monomer dropping rate, and feeding sequence. ① Polymerization temperature determines the initiator decomposition rate and polymer molecular weight, thus affecting the stability of the polymerization reaction and the molecular chain structure of the product; ② Monomer dropping rate regulates the monomer concentration and reaction rate of the polymerization system, controlling the nucleation and growth process of emulsion particles, making the particle size distribution concentrated and controllable; ③ Siloxane coupling agents are introduced using a gradient grafting method, and by controlling their addition amount and dropping timing, grafting efficiency and crosslinking density are adjusted to achieve precise control of the degree of functionalization of polymer chains; ④ Nano-silica is slowly added after pH pre-adjustment, allowing the particles to be uniformly dispersed in the emulsion and fully hybridized with the polymer matrix, ensuring the integrity and uniformity of the hybrid structure. The coordinated operation of various process parameters enriches soft monomers in the core layer and hard monomers in the shell layer, forming a gradient distribution of internal flexibility and external rigidity in the particles. At the same time, it achieves an organic combination of siloxane gradient grafting and in-situ hybridization of nano-silica, providing process assurance for the construction of the core-shell structure and organic-inorganic interpenetrating network of emulsion particles.

[0074] 6. Synergistic effect mechanism of preparation process

[0075] The precise compartmentalized batching process separates and stores powder, fiber, emulsion and water, avoiding the agglomeration and clumping problems caused by premature fiber feeding, and also avoiding local clumping caused by premature contact between emulsion and dry powder. This ensures accurate metering of each component and stable initial state, providing a foundation for subsequent uniform dispersion.

[0076] The segmented high-speed mixing process employs a step-by-step feeding and segmented mixing method. First, dry mixing of the powders ensures uniform mixing of the cementitious materials, aggregates, and powdered additives, forming a homogeneous powder system. Next, fibers of different sizes are added and dry-mixed, utilizing the friction and collision of powder particles to fully disperse the fibers and prevent clumping. Finally, water and emulsion are added for wet mixing, ensuring the liquid phase components are evenly distributed throughout the powder and fiber system, forming a homogeneous plastic mixture. This segmented mixing mode is well-suited to the multi-component, low water-to-binder ratio, and high fiber content characteristics of the materials in this invention, ensuring the uniformity and stability of the mixture.

[0077] Vacuum extrusion molding process uses a negative pressure environment to extract air trapped inside the mixture, reducing porosity defects and improving the initial density of the matrix; at the same time, the screw shearing and extrusion pressure of the extruder makes the particles pack more tightly, ensuring the density and dimensional accuracy of the preform.

[0078] The ambient temperature static curing and natural curing process, combined with the ambient temperature hydration activation characteristics of the material system, eliminates the need for additional heating, humidification, or high pressure, simplifying the production process and reducing energy consumption. During the early stages of pre-curing, hydration proceeds smoothly, and strength gradually increases to the demolding threshold. In the natural curing stage after demolding, the long-term activating effect of the composite cementitious system continues, the pozzolanic reaction continues, and the strength steadily increases in the later stages, while the matrix density continuously improves, ultimately forming a high-performance finished board.

[0079] The entire process is interconnected and highly compatible, working synergistically with the characteristics of the material system to ensure the stable and efficient preparation of ultra-high performance extruded cement fiberboard under autoclaving-free conditions. Attached Figure Description

[0080] Figure 1 This is a flowchart illustrating the process for preparing the autoclaved aerated ultra-high performance extruded cement fiberboard of this invention.

[0081] Figure 2 This is a comparison chart of the autoclaved aerated ultra-high performance extruded cement fiberboard of this invention and the amount of cellulose ether used in traditional ECP;

[0082] Figure 3 This is a schematic diagram of the ternary composite fiber reinforcement system and pseudo-ductile failure zone of the autoclaved ultra-high performance extruded cement fiberboard of the present invention.

[0083] Figure 4 This refers to the autoclaved aerated concrete fiberboard (AACF) obtained in Example 2 of this invention.

[0084] Figure 5 This is a bar chart comparing the time required for Embodiments 1-3 of the present invention to reach demolding strength with Comparative Example 1;

[0085] Figure 6This is a bar chart comparing the core material properties of Example 2 and Comparative Example 1 of the present invention. Detailed Implementation

[0086] To make the technical solution and advantages of the present invention clearer, the present invention will be further described in detail below with reference to specific embodiments and comparative examples. The following embodiments are used to illustrate the technical solution of the present invention. Simple deductions and substitutions made by those skilled in the art based on the core concept of the present invention are all within the protection scope of the present invention.

[0087] All examples and comparative examples used the same test baseline conditions to eliminate interference from variables such as environment, equipment, and specifications, ensuring the comparability and reproducibility of test data: the curing environment temperature was 20±5℃, and the relative humidity was 60~70%; the standard thickness of the finished board was 12mm; the same vacuum extrusion molding equipment was used; all test samples were taken from the middle of the board; each test group had no less than 3 parallel samples, and the test results were taken as the arithmetic mean.

[0088] Example 1

[0089] An organic-inorganic hybrid modified styrene-acrylic polymer emulsion comprises the following raw materials: 25% butyl acrylate, 15% methyl methacrylate, 12% styrene, 3% γ-methacryloyloxypropyltrimethoxysilane, 8% acidic nano silica sol (30% solid content, particle size 10-20 nm), 2% polyvinyl alcohol (88% degree of alcoholysis), 1.5% sodium dodecyl sulfate, 1.0% nonylphenol polyoxyethylene ether, 0.3% ammonium persulfate, 0.2% sodium bicarbonate, and the remainder being deionized water.

[0090] An organic-inorganic hybrid modified styrene-acrylic polymer emulsion was prepared by seed emulsion polymerization, and the specific preparation steps are as follows:

[0091] Step 1: Preparation of pre-emulsion. Add SDS, OP-10, and PVA to deionized water and stir to dissolve, forming an emulsifier aqueous solution. Mix BA, MMA, and St according to the specified ratio and slowly add them dropwise to the emulsifier aqueous solution. Continue stirring for 30 minutes to prepare a stable pre-emulsion. Then add KH-570 siloxane coupling agent and continue stirring for 15 minutes to ensure that the coupling agent is evenly dispersed in the pre-emulsion.

[0092] Step 2: Seed emulsion polymerization initiation. Take 10% of the total amount of pre-emulsion and add it to the reactor. Heat to 78°C, add 10% of APS initiator and all of the NaHCO3 buffer, and react for 20 minutes to form a light blue seed emulsion.

[0093] Step 3: Gradient grafting modification with organosiloxanes. The remaining pre-emulsion and APS initiator solution were added dropwise to the reactor at a constant flow rate using a constant flow pump, with the total addition time controlled at 3 hours and the reaction temperature maintained at 80°C.

[0094] Step 4: In-situ hybridization and recombination of nano-silica. After the monomer is added, the pH of the acidic nano-silica sol is adjusted to 8-9 with dilute ammonia, and then slowly added dropwise to the reaction system. The reaction is then maintained at this temperature for 1.5 hours.

[0095] Step 5: Post-treatment and aging stabilization. After the heat treatment is completed, the temperature is lowered to 60℃, and a redox initiation system composed of tert-butyl hydrogen peroxide and sodium formaldehyde sulfoxylate is added for post-elimination treatment for 30 min to reduce the residual monomer content to ≤0.1%; then the temperature is further lowered to ≤40℃ for aging stabilization for 2 h.

[0096] Step Six: Filtration, Solids Adjustment, and Quality Inspection. The emulsion is filtered through a 100-mesh filter to remove coagulations. The solids content is adjusted to 50±1% with deionized water to obtain an organic-inorganic hybrid modified styrene-acrylic polymer emulsion.

[0097] A non-autoclaved ultra-high performance extruded cement fiberboard and its preparation method include the following steps:

[0098] (1) Precise batching and dispensing: Weigh out 100 parts of 52.5 ordinary Portland cement, 15 parts of silica fume, 10 parts of Class I fly ash, and other materials with a specific surface area ≥450m². 2 The mixture consists of 5 parts / kg of γ-type dicalcium silicate micro powder, 50 parts of 40-60 mesh quartz sand, 30 parts of 80-100 mesh quartz sand, 20 parts of 400 mesh quartz powder, 20 parts of 12-15mm copper-plated steel fiber, 2 parts of 6-9mm basalt fiber, 2 parts of coniferous wood fiber, 1.0 part of powdered polycarboxylate superplasticizer, 0.1 part of cellulose ether with a viscosity of 20000-40000mPa·s, 6 parts of organic-inorganic hybrid modified styrene-acrylic polymer emulsion with a solid content of 50%, 0.5 parts of calcium formate, 0.03 parts of sodium gluconate, and 20 parts of water, with a water-to-binder ratio of 0.177. All raw materials are stored in separate compartments and measured independently. Low-dosage fibers and trace additives are weighed separately and accurately to ensure accurate proportions.

[0099] (2) Segmented high-speed mixing: All powder raw materials were put into a twin-shaft high-speed mixer, the blade linear velocity was set to 2.5 m / s, and the dry mixing mode was turned on for 3 minutes to fully mix the various powders. After the dry mixing was completed, softwood fiber and basalt fiber were added in sequence and dry-mixed for 2 minutes. Finally, all copper-plated steel fiber was added in a slow and uniform manner and dry-mixed for 2 minutes to fully disperse the three different sizes of fibers in the powder system. After the fibers were dispersed, mixing water was added in two batches, and the mixture was stirred for 1 minute after each addition, for a total of 2 minutes of stirring to initially disperse the water. Then, organic-inorganic hybrid modified styrene-acrylic polymer emulsion was added and wet-mixed for 4 minutes to finally obtain a mixture with no bleeding, no stratification, and uniform plasticity.

[0100] (3) Vacuum extrusion molding: The prepared mixture is fed into a vacuum extruder for extrusion molding. The vacuum degree of the extruder is adjusted to -0.06MPa, the extrusion speed is set to 0.8m / min, the screw speed is 18r / min, and the forming die pressure is 1.0MPa. A complete blank with a thickness of 12mm is obtained by continuous extrusion molding.

[0101] (4) Pre-curing at room temperature: Place the formed blank and the tray together in a room temperature environment of 20±5℃ and 60~70% relative humidity for pre-curing. No need to cover with a film to keep it moist or add heat for curing. Maintain a natural ventilation environment throughout the process.

[0102] (5) Rapid demolding: After pre-curing for 4 hours, the compressive strength of the blank is tested to be 12.3 MPa, which meets the demolding requirements. Demolding and transfer operations are then carried out.

[0103] (6) Natural curing at room temperature: After demolding, the boards are stacked in the open air under the same room temperature environment and naturally cured for 28 days. No additional watering or heat preservation is required during the curing process.

[0104] (7) Cutting and finishing: After curing, the board is cut to a fixed length, the four sides are sealed and polished, the samples with edge defects are removed, and after sampling and testing various performance, it is put into storage to obtain the finished product of autoclaved aerated ultra-high performance extruded cement fiber board.

[0105] Example 2

[0106] An organic-inorganic hybrid modified styrene-acrylic polymer emulsion comprises the following raw materials: 27.5% butyl acrylate, 17.5% methyl methacrylate, 14% styrene, 4.5% γ-methacryloyloxypropyltrimethoxysilane, 10% acidic nano silica sol (30% solid content, particle size 10-20 nm), 3% polyvinyl alcohol (88% degree of alcoholysis), 2.0% sodium dodecyl sulfate, 1.5% nonylphenol polyoxyethylene ether, 0.5% ammonium persulfate, 0.35% sodium bicarbonate, and the remainder being deionized water.

[0107] An organic-inorganic hybrid modified styrene-acrylic polymer emulsion was prepared by seed emulsion polymerization, and the specific preparation steps are as follows:

[0108] Step 1: Preparation of pre-emulsion. Add SDS, OP-10, and PVA to deionized water and stir to dissolve, forming an emulsifier aqueous solution. Mix BA, MMA, and St according to the specified ratio, and slowly add them dropwise to the emulsifier aqueous solution. Continue stirring for 35 minutes to prepare a stable pre-emulsion. Then add KH-570 siloxane coupling agent and continue stirring for 18 minutes to ensure that the coupling agent is evenly dispersed in the pre-emulsion.

[0109] Step 2: Seed emulsion polymerization initiation. Take 12% of the total amount of pre-emulsion and add it to the reactor. Heat to 80°C, add 12% of APS initiator and all of the NaHCO3 buffer, and react for 25 minutes to form a light blue seed emulsion.

[0110] Step 3: Gradient grafting modification with organosiloxanes. The remaining pre-emulsion and APS initiator solution were added dropwise to the reactor at a constant flow rate using a constant flow pump, with the total dropping time controlled at 3.5 h and the reaction temperature maintained at 83 °C.

[0111] Step 4: In-situ hybridization and recombination of nano-silica. After the monomer is added, the pH of the acidic nano-silica sol is adjusted to 8-9 with dilute ammonia, and then slowly added dropwise to the reaction system. The reaction is then maintained at this temperature for 1.8 hours.

[0112] Step 5: Post-treatment and aging stabilization. After the heat treatment is completed, the temperature is lowered to 62°C, and a redox initiation system composed of tert-butyl hydrogen peroxide and sodium formaldehyde sulfoxylate is added for post-elimination treatment for 35 min to reduce the residual monomer content to ≤0.1%; then the temperature is further lowered to ≤40°C for aging stabilization for 2.5 h.

[0113] Step Six: Filtration, Solids Adjustment, and Quality Inspection. The emulsion is filtered through a 100-mesh filter to remove coagulations. The solids content is adjusted to 50±1% with deionized water to obtain an organic-inorganic hybrid modified styrene-acrylic polymer emulsion.

[0114] A non-autoclaved ultra-high performance extruded cement fiberboard and its preparation method include the following steps:

[0115] (1) Precise batching and dispensing: Weigh out 100 parts of 52.5 ordinary Portland cement, 20 parts of silica fume, 15 parts of Class I fly ash, and other materials with a specific surface area ≥450m². 2The mixture consists of 8 parts / kg of γ-type dicalcium silicate micro powder, 60 parts of 40-60 mesh quartz sand, 40 parts of 80-100 mesh quartz sand, 25 parts of 400 mesh quartz powder, 30 parts of 12-15mm copper-plated steel fiber, 3 parts of 6-9mm basalt fiber, 2.5 parts of coniferous wood fiber, 1.5 parts of powdered polycarboxylate superplasticizer, 0.2 parts of cellulose ether with a viscosity of 20000-40000mPa·s, 9 parts of organic-inorganic hybrid modified styrene-acrylic polymer emulsion with a solid content of 50%, 1.0 part of calcium formate, 0.05 parts of sodium gluconate, and 22 parts of water, with a water-to-binder ratio of 0.185. All raw materials are stored in separate compartments and measured independently. Low-dosage fibers and trace additives are weighed separately and accurately to ensure accurate proportions.

[0116] (2) Segmented high-speed mixing: All powder raw materials were put into a twin-shaft high-speed mixer, the blade linear velocity was set to 3.0 m / s, and the dry mixing mode was turned on for 4 minutes to fully mix the various powders. After the dry mixing was completed, coniferous wood fiber and basalt fiber were added in sequence and dry-mixed for 2 minutes. Finally, all copper-plated steel fiber was added in a slow and uniform manner and dry-mixed for 3 minutes to fully disperse the three different sizes of fibers in the powder system. After the fibers were dispersed, mixing water was added in two batches, and the mixture was stirred for 1 minute after each addition, for a total of 2 minutes of stirring to initially disperse the water. Then, organic-inorganic hybrid modified styrene-acrylic polymer emulsion was added and wet-mixed for 5 minutes to finally obtain a mixture with no bleeding, no stratification, and uniform plasticity.

[0117] (3) Vacuum extrusion molding: The prepared mixture is fed into a vacuum extruder for extrusion molding. The vacuum degree of the extruder is adjusted to -0.07MPa, the extrusion speed is set to 1.2m / min, the screw speed is 22r / min, and the die pressure is 1.2MPa. A complete blank with a thickness of 12mm is obtained by continuous extrusion molding.

[0118] (4) Pre-curing at room temperature: Place the formed blank and the tray together in a room temperature environment of 20±5℃ and 60~70% relative humidity for pre-curing. No need to cover with a film to keep it moist or add heat for curing. Maintain a natural ventilation environment throughout the process.

[0119] (5) Rapid demolding: After pre-curing for 2 hours, the compressive strength of the blank is tested to be 14.1 MPa, which meets the demolding requirements. Demolding and transfer operations are then carried out.

[0120] (6) Natural curing at room temperature: After demolding, the boards are stacked in the open air under the same room temperature environment and naturally cured for 28 days. No additional watering or heat preservation is required during the curing process.

[0121] (7) Cutting and finishing: After curing, the boards are cut to a fixed length, the four sides are sealed and sanded, samples with edge defects are removed, and after sampling for various performance tests, they are put into storage, thus obtaining the following: Figure 4The finished product shown is an autoclaved, high-performance extruded cement fiberboard.

[0122] Example 3

[0123] An organic-inorganic hybrid modified styrene-acrylic polymer emulsion comprises the following raw materials: 30% butyl acrylate, 20% methyl methacrylate, 18% styrene, 6% γ-methacryloyloxypropyltrimethoxysilane, 12% acidic nano silica sol (30% solid content, particle size 10-20 nm), 4% polyvinyl alcohol (88% degree of alcoholysis), 2.5% sodium dodecyl sulfate, 2.0% nonylphenol polyoxyethylene ether, 0.8% ammonium persulfate, 0.5% sodium bicarbonate, and the remainder being deionized water.

[0124] An organic-inorganic hybrid modified styrene-acrylic polymer emulsion was prepared by seed emulsion polymerization, and the specific preparation steps are as follows:

[0125] Step 1: Preparation of pre-emulsion. SDS, OP-10 and PVA are added to deionized water and stirred to dissolve, forming an emulsifier aqueous solution. BA, MMA and St are mixed evenly according to the ratio and then slowly added dropwise to the emulsifier aqueous solution. Stirring is continued for 40 minutes to prepare a stable pre-emulsion. Subsequently, KH-570 siloxane coupling agent is added and stirring is continued for 20 minutes to ensure that the coupling agent is evenly dispersed in the pre-emulsion.

[0126] Step 2: Seed emulsion polymerization initiation. Take 15% of the total amount of pre-emulsion and add it to the reactor. Heat to 82°C, add 15% of APS initiator and all of the NaHCO3 buffer, and react for 30 minutes to form a light blue seed emulsion.

[0127] Step 3: Gradient grafting modification with organosiloxanes. The remaining pre-emulsion and APS initiator solution were added dropwise to the reactor at a constant flow rate using a constant flow pump, with the total addition time controlled at 4 hours and the reaction temperature maintained at 85℃.

[0128] Step 4: In-situ hybridization and recombination of nano-silica. After the monomer is added, the pH of the acidic nano-silica sol is adjusted to 8-9 with dilute ammonia, and then slowly added dropwise to the reaction system. The reaction is then maintained at this temperature for 2 hours.

[0129] Step 5: Post-treatment and aging stabilization. After the heat treatment is completed, the temperature is lowered to 65℃, and a redox initiation system composed of tert-butyl hydrogen peroxide and sodium formaldehyde sulfoxylate is added for post-elimination treatment for 40 min to reduce the residual monomer content to ≤0.1%; then the temperature is further lowered to ≤40℃ for aging stabilization for 3 h.

[0130] Step Six: Filtration, Solids Adjustment, and Quality Inspection. The emulsion is filtered through a 100-mesh filter to remove coagulations. The solids content is adjusted to 50±1% with deionized water to obtain an organic-inorganic hybrid modified styrene-acrylic polymer emulsion.

[0131] A non-autoclaved ultra-high performance extruded cement fiberboard and its preparation method include the following steps:

[0132] (1) Precise batching and dispensing: Weigh out 100 parts of 52.5 ordinary Portland cement, 25 parts of silica fume, 20 parts of Class I fly ash, and other materials with a specific surface area ≥450m². 2 The mixture consists of 10 parts / kg of γ-type dicalcium silicate micro powder, 70 parts of 40-60 mesh quartz sand, 50 parts of 80-100 mesh quartz sand, 30 parts of 400 mesh quartz powder, 40 parts of 12-15mm copper-plated steel fiber, 4 parts of 6-9mm basalt fiber, 3 parts of coniferous wood fiber, 2.0 parts of powdered polycarboxylate superplasticizer, 0.3 parts of cellulose ether with a viscosity of 20000-40000mPa·s, 12 parts of organic-inorganic hybrid modified styrene-acrylic polymer emulsion with a solid content of 50%, 1.5 parts of calcium formate, 0.08 parts of sodium gluconate, and 25 parts of water, with a water-to-binder ratio of 0.20. All raw materials are stored in separate compartments and measured independently. Low-dosage fibers and trace additives are weighed separately and accurately to ensure accurate proportions.

[0133] (2) Segmented high-speed mixing: All powder raw materials were put into a twin-shaft high-speed mixer, the blade linear velocity was set to 3.5 m / s, and the dry mixing mode was turned on for 5 minutes to ensure that the various powders were fully mixed. After the dry mixing was completed, softwood fiber and basalt fiber were added in sequence and dry-mixed for 3 minutes. Then, copper-plated steel fiber was evenly sprinkled in 3 times, and dry-mixed for about 1.3 minutes after each addition, for a total of 4 minutes of dry mixing, so that the three different sizes of fibers were fully dispersed in the powder system. After the fibers were dispersed, mixing water was added in three times, and stirred for 1 minute after each addition, for a total of 3 minutes of stirring to initially disperse the water. Then, organic-inorganic hybrid modified styrene-acrylic polymer emulsion was added and wet-mixed for 6 minutes to finally obtain a mixture with no bleeding, no stratification, and uniform plasticity.

[0134] (3) Vacuum extrusion molding: The prepared mixture is fed into a vacuum extruder for extrusion molding. The vacuum degree of the extruder is adjusted to -0.09MPa, the extrusion speed is set to 1.5m / min, the screw speed is 28r / min, and the forming die pressure is 1.4MPa. A complete blank with a thickness of 12mm is obtained by continuous extrusion molding.

[0135] (4) Pre-curing at room temperature: Place the formed blank and the tray together in a room temperature environment of 20±5℃ and 60~70% relative humidity for pre-curing. No need to cover with a film to keep it moist or add heat for curing. Maintain a natural ventilation environment throughout the process.

[0136] (5) Rapid demolding: After pre-curing for 2 hours, the compressive strength of the blank is tested to be 13.5 MPa, which meets the demolding requirements. Demolding and transfer operations are then carried out.

[0137] (6) Natural curing at room temperature: After demolding, the boards are stacked in the open air under the same room temperature environment and naturally cured for 28 days. No additional watering or heat preservation is required during the curing process.

[0138] (7) Cutting and finishing: After curing, the board is cut to a fixed length, the four sides are sealed and polished, the samples with edge defects are removed, and after sampling and testing various performance, it is put into storage to obtain the finished product of autoclaved aerated ultra-high performance extruded cement fiber board.

[0139] Comparative Example 1 (Traditional autoclaving single-fiber ECP system)

[0140] This comparative example uses a conventional benchmark system for autoclaved aerated concrete (ECP) fiberboard, employing a high-temperature, high-pressure autoclaving curing method. By weight, the components are: 100 parts 52.5 ordinary Portland cement, 10 parts silica fume, 8 parts fly ash, 80 parts quartz sand, 1.0 part cellulose ether, 4 parts coniferous wood fiber, excluding copper-plated steel fiber, basalt fiber, organic-inorganic hybrid modified styrene-acrylic polymer emulsion, and 32 parts water. All powder raw materials and coniferous wood fiber are dry-mixed evenly, then wet-mixed with water until extrusion plasticity is achieved. The mixture is then formed into 12mm thick blanks using a vacuum extruder. After pre-curing at room temperature, the blanks are autoclaved at 175℃ under saturated steam pressure for 10 hours. After cooling and depressurization, the blanks are demolded and naturally cured for 28 days. Samples are then cut and tested, serving as a performance comparison benchmark for conventional autoclaved ECP boards.

[0141] Comparative Example 2 (Hybrid emulsion removed, highly cellulose ether-based system)

[0142] Based on Example 2, this comparative example omits the organic-inorganic hybrid modified styrene-acrylic polymer emulsion component and increases the cellulose ether content to 1.2 parts by weight. The remaining gelling system, aggregate system, fiber system, and basic auxiliary agent components are completely consistent with those in Example 2. A room temperature natural curing mode is used to verify the synergistic effect of the composite polymer emulsion system.

[0143] Comparative Example 3 (Single fiber system containing only wood fiber)

[0144] Based on Example 2, this comparative example omits the copper-plated steel fiber and basalt fiber components, retaining only 3 parts by weight of coniferous wood fiber. The remaining cementitious system, aggregate system, and polymer additive system are completely consistent with those of Example 2. A room temperature natural curing mode is used to verify the synergistic toughening effect of multi-scale composite fibers.

[0145] Performance testing and results analysis

[0146] I. Testing Basis and Methods

[0147] 1. Early demolding compressive strength: GB / T 7019-2024 "Test Methods for Fiber Cement Products" was followed. Extruded blanks pre-cured to the set age were cut into standard test blocks of 100mm×100mm×12mm. A microcomputer-controlled pressure testing machine was used to uniformly load the specimens at a rate of 0.5MPa / s. The failure load of the specimens was recorded and the compressive strength was calculated. The average value of 3 parallel specimens in each group was taken. The industry-standard demolding strength threshold is ≥12MPa.

[0148] 2.28d Mechanical Properties: The test shall be conducted in accordance with GB / T 7019-2024 "Test Methods for Fiber Cement Products". The compressive strength shall be tested using the above-mentioned standard test blocks; the flexural strength shall be tested using the three-point bending test method with a test span of 200 mm and a loading rate of 0.2 mm / min; the impact strength shall be tested using a 5 kg standard steel ball drop hammer impact test, with the drop height gradually increased, and the critical impact energy at which the board completely breaks shall be recorded and converted into the impact energy value per unit area.

[0149] 3. Water absorption rate and average porosity of the matrix: GB / T 7019-2024 "Test Methods for Fiber Cement Products" shall be followed. The water absorption rate shall be calculated by the mass difference after drying to constant weight and soaking in clean water at room temperature for 24 hours. The porosity shall be calculated by vacuum saturated weighing method, and the average porosity of the matrix shall be calculated by true density and apparent density.

[0150] 4. Freeze-thaw cycle performance: GB / T 50082-2024 "Standard for Test Methods of Long-term Performance and Durability of Concrete" was implemented. 50 freeze-thaw cycles were conducted using the rapid freezing method, with a temperature range of -20~20℃ for each cycle. After the test, the compressive strength was tested and the strength retention rate was calculated.

[0151] 5. Chloride ion penetration performance: GB / T 50082-2024 "Standard for Test Methods of Long-term Performance and Durability of Concrete" was adopted. The RCM rapid chloride ion migration method was used to prepare cylindrical samples with a diameter of φ100mm×50mm. After vacuum saturation, a constant DC voltage of 30V was applied to test the chloride ion penetration depth and calculate the unsteady chloride ion migration coefficient of the material to characterize the ion penetration resistance and durability of the board.

[0152] 6. Production Energy Consumption and Pallet Turnover Efficiency: Industrial-grade smart energy meters are used to measure the energy consumption of each batch of products throughout the entire process of mixing, extrusion, curing, and finishing. Combined with the formed volume of the sheet material, the energy consumption per unit volume (kWh / m³) is calculated. 3 For traditional autoclaved ECP sheets, the steam consumption of the autoclave and the energy consumption of related equipment are calculated separately. A fixed number of pallets are used, and the number of pallet demolding turnovers within 24 hours is recorded. The turnover efficiency is compared with that of the traditional process, and the efficiency improvement rate is calculated. All tests use industrially common measurement standards.

[0153] 7. Microstructure observation: The cut surface of the 28-day-old sample was taken, and after gold sputtering pretreatment, the micromorphology, pore structure and fiber-matrix interface bonding state of the matrix were observed using a scanning electron microscope at a magnification of 500 to 2000 times.

[0154] II. Test Results

[0155] Performance tests were conducted on the examples and comparative examples, and the test data are detailed in Tables 1 to 4. To visually compare the performance differences of each group of samples, plots were generated based on the test data. Figure 5 , Figure 6 .

[0156] Table 1. Early demolding strength test results of Examples 1-3 and Comparative Examples 1-3

[0157]

[0158] Table 2. Test results of mechanical and physical properties of Examples 1-3 and Comparative Examples 1-3 after 28 days.

[0159]

[0160] Table 3. Durability test results of Examples 1-3 and Comparative Example 1

[0161]

[0162] Table 4 Comparison of production energy consumption and pallet turnover efficiency in Examples 1-3 and Comparative Example 1

[0163]

[0164] III. Results Analysis and Creative Verification

[0165] 1. Early strength and demolding performance analysis

[0166] As can be seen from the data in Table 1, the early strength development rate of the three sets of embodiments of the present invention is much higher than that of the three comparative examples. Examples 2 and 3 can reach the demolding strength (compressive strength ≥12.0MPa) after 2 hours of pre-curing, and Example 1 can also meet the demolding requirements after 4 hours. However, Comparative Example 1 with traditional autoclaving process requires 16 hours to demold, Comparative Example 2 without emulsion and high cellulose ether content requires 12 hours, and Comparative Example 3 with single fiber system also requires 8 hours.

[0167] Based on the aforementioned technical principles, the rapid early strength development of this invention is the result of the synergistic effect of three mechanisms: the elimination of hydration inhibition by low-dosage cellulose ether, the early strength activation by calcium formate, and the early film-forming skeleton of the hybrid emulsion. Comparative Examples 1 and 2 both used high-dosage cellulose ethers. The long polymer chains encapsulating the gel particles severely hindered the hydration process. Even though Comparative Example 2 retained both the composite gel system and the fiber system, its early strength development was still very slow, fully demonstrating that high-dosage cellulose ether is the core factor restricting early strength. Although Comparative Example 3 used low-dosage cellulose ethers and a composite gel system, it lacked the early skeletal support of steel fibers and basalt fibers, and its early strength was also lower than that of the embodiments of this invention.

[0168] 2. Mechanical property analysis

[0169] From Table 2 and Figure 6 It can be seen that the 28-day compressive strength of the three embodiments of the present invention is all >100MPa, the flexural strength is all >18MPa, and the impact strength is all >15kJ / m. 2 The results were significantly better than those of Comparative Examples 1-3. Among them, Example 2 showed the best overall mechanical properties, with a compressive strength of 116.3 MPa, which was 166.74% higher than that of Comparative Example 1, a flexural strength that was 143.68% higher, and an impact resistance that was 259.62% higher.

[0170] Based on the analysis of the technical principles, the ultra-high mechanical properties of this invention originate from the multiple synergistic effects of multi-level particle packing, complete hydration of composite gels, and multi-scale fiber synergistic toughening. In Comparative Example 2, after removing the hybrid emulsion and highly doping with cellulose ether, the strength decreased due to the cellulose ether inhibiting hydration; furthermore, the lack of the interfacial reinforcement effect of the emulsion weakened the bond between the fiber and the matrix, resulting in a significant decrease in mechanical properties. This demonstrates that the composite polymer emulsion not only provides lubrication but also significantly enhances mechanical strength. Comparative Example 3, retaining only single wood fibers, lacks the macroscopic load-bearing capacity of steel fibers and the microscopic crack-resistant effect of basalt fibers, resulting in a very limited toughening effect and a significant decrease in flexural and impact resistance. This proves that the synergistic toughening of multi-scale composite fibers is key to improving toughness and strength.

[0171] 3. Physical and Durability Performance Analysis

[0172] From Table 2, Table 3 and Figure 6 As can be seen, the water absorption rate and average matrix porosity of the embodiments of the present invention are much lower than those of Comparative Examples 1 to 3, and the strength retention rate and chloride ion impermeability after 50 freeze-thaw cycles are also significantly better than those of Comparative Example 1. The porosity of Comparative Example 1 is as high as 18.6%, with a large number of interconnected capillaries, resulting in high water absorption and poor impermeability and freeze-thaw resistance; while the porosity of the embodiments of the present invention is only 2.8 to 4.2%, and the matrix is ​​relatively dense, thus exhibiting excellent durability.

[0173] Based on the analysis of technical principles, the extremely dense matrix structure originates from the gradation design of the densest packing of multi-level particles, and the pore-filling effect of the high-density hydration products generated by the full hydration of the composite cementitious system. The dense matrix structure blocks the intrusion channels of external moisture and corrosive ions, resulting in low water absorption, strong impermeability, weak freeze-thaw damage during freeze-thaw cycles, and difficulty for acid and alkali corrosive media to penetrate deep into the matrix, significantly improving the long-term service stability of the board. Comparative Examples 2 and 3, due to insufficient hydration or numerous fiber interface defects, have significantly higher porosity and water absorption rates than the embodiments of this invention, and their durability is correspondingly reduced.

[0174] 4. Production Energy Consumption and Efficiency Analysis

[0175] As can be seen from the data in Table 4, the unit volume production energy consumption of the present invention embodiment is only about 15% of that of the traditional autoclaving process (Comparative Example 1), with an energy consumption reduction of more than 80%, and the energy saving effect is extremely significant; the pallet turnover efficiency is increased by 200~300%, and the production capacity efficiency is greatly improved.

[0176] The significant reduction in energy consumption is entirely due to the autoclaving-free process design, which eliminates the energy-intensive autoclaving curing process, retaining only the electricity consumption of conventional processes such as ingredient mixing, stirring, extrusion, and cutting. The improved turnover efficiency comes from rapid demolding technology; the increased number of pallet turnovers directly increases the capacity of each production line and reduces the production cost per unit product.

[0177] 5. Microstructure verification

[0178] As can be seen from Tables 2 and 3, Comparative Example 1 has an average matrix porosity as high as 18.6%, a water absorption rate of 13.8%, and a chloride ion permeability coefficient of 1.36 × 10⁻⁶. -12 m 2 The / s indicates the presence of numerous interconnected capillary pores within the matrix, resulting in poor matrix density and easy penetration of corrosive ions and moisture along the pores. In Examples 1-3 of this invention, the average porosity of the matrix is ​​only 2.8-4.2%, the water absorption rate is as low as 3.6-4.8%, and the chloride ion permeability coefficient is only 0.21-0.24×10⁻⁶. -12 m 2 / s, the large-sized interconnected pores inside the matrix are significantly reduced, and the pore structure is mainly composed of small closed pores, which verifies the structural advantages of the present invention in terms of high strength, low permeability and high durability from the microstructure level.

[0179] 6. Creative Synthesis Analysis

[0180] The comparison between the examples and comparative examples shows that the technical effects of this invention are not due to improvements in a single component or process, but rather the result of the synergistic effect of five major modules: the gel activation system, the aggregate gradation system, the fiber reinforcement system, the polymer rheology system, and the preparation process system. Eliminating the composite emulsion would prevent stable extrusion and strength enhancement at low ether content; eliminating the multi-scale fibers would prevent the achievement of high strength and high toughness; eliminating the composite gel activation would prevent sufficient hydration without autoclaving; and the lack of multi-stage close-packed gradation would prevent the achievement of extreme matrix density. The substitution or deletion of any single feature cannot achieve the comprehensive technical effects of this invention: "autoclaving-free, fast demolding, ultra-high strength, high durability, and high efficiency."

[0181] The above content should not be construed as limiting the specific implementation of this invention to these descriptions. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of this invention, and all such deductions or substitutions should be considered as falling within the patent protection scope defined by the submitted claims.

Claims

1. A non-autoclaved, high-performance extruded cement fiberboard, characterized in that, Based on 100 parts by weight of 52.5 ordinary Portland cement, it includes the following components: Cementitious components: 15-25 parts silica fume, 10-20 parts Class I fly ash, 5-10 parts calcium silicate; Aggregate composition: 50-70 parts of 40-60 mesh quartz sand, 30-50 parts of 80-100 mesh quartz sand, and 20-30 parts of 400 mesh quartz powder; Reinforcing fibers: 20-40 parts of copper-plated steel fiber with a length of 12-15mm, 2-4 parts of basalt fiber with a length of 6-9mm, and 2-3 parts of coniferous wood fiber; Chemical admixtures: 1.0-2.0 parts of powdered polycarboxylate superplasticizer, 0.1-0.3 parts of cellulose ether, 6-12 parts of organic-inorganic hybrid modified styrene-acrylic polymer emulsion with 50% solid content, 0.5-1.5 parts of calcium formate, and 0.03-0.08 parts of sodium gluconate; 20-25 parts of mixing medium; The cement fiberboard is produced by vacuum extrusion molding and natural curing at room temperature, without any autoclaving process.

2. The autoclaved aerated concrete (AAC) high-performance extruded cement fiberboard according to claim 1, characterized in that, The viscosity of the cellulose ether is 20,000~40,000 mPa·s; the calcium silicate is γ-type dicalcium silicate micro powder with a specific surface area ≥450 m². 2 / kg; the mixing medium is water.

3. The autoclaved aerated concrete (AAC) high-performance extruded cement fiberboard according to claim 1, characterized in that, The organic-inorganic hybrid modified styrene-acrylic polymer emulsion is prepared by seed emulsion polymerization of butyl acrylate, methyl methacrylate, styrene, γ-methacryloyloxypropyltrimethoxysilane, and acidic nano silica sol.

4. The autoclaved aerated concrete (AAC) high-performance extruded cement fiberboard according to claim 3, characterized in that, The raw materials of the organic-inorganic hybrid modified styrene-acrylic polymer emulsion, by mass percentage, include: 25-30% butyl acrylate, 15-20% methyl methacrylate, 12-18% styrene, 3-6% γ-methacryloyloxypropyltrimethoxysilane, 8-12% acidic nano silica sol with a solid content of 30%, 2-4% polyvinyl alcohol, 1.5-2.5% sodium dodecyl sulfate, 1.0-2.0% nonylphenol polyoxyethylene ether, 0.3-0.8% ammonium persulfate, 0.2-0.5% sodium bicarbonate, and the balance being deionized water.

5. The autoclaved aerated concrete (AAC) high-performance extruded cement fiberboard according to claim 1, characterized in that, The total water-cement ratio of the cement fiberboard is 0.17~0.20, and the total water includes the mixing water and the water introduced by the organic-inorganic hybrid modified styrene-acrylic polymer emulsion.

6. A method for preparing autoclaved aerated concrete (AAC) ultra-high performance extruded cement fiberboard as described in any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Precise compartmentalization and batching: Weigh each powder raw material, reinforcing fiber, chemical additives and mixing water according to the ratio, store them in separate compartments and measure them independently; (2) Segmented high-speed mixing: First, dry mix the powder raw materials evenly, then add the reinforcing fiber and dry mix to disperse, and finally add the mixing water and organic-inorganic hybrid modified styrene-acrylic polymer emulsion for wet mixing to obtain plastic mixture; (3) Vacuum extrusion molding: The mixture is fed into a vacuum extruder and continuously extruded under negative pressure to obtain a billet; (4) Pre-curing at room temperature: Place the billet in a room temperature environment for pre-curing; (5) Rapid demolding: Demolding is performed after the compressive strength of the blank reaches the demolding strength; (6) Natural curing at room temperature: After demolding, the boards are cured at room temperature until the target age. (7) Cutting and finishing: The finished product is obtained by cutting the cured board to a fixed length and sealing the edges.

7. The method for preparing autoclaved aerated concrete (AAC) ultra-high performance extruded cement fiberboard according to claim 6, characterized in that, In step (2), the blade linear velocity of the dry mixing is 2.5~3.5m / s, the dry mixing time of the powder is 3~5min; the reinforcing fiber is added in batches, the total dry mixing time is 4~7min; the wet mixing time is 4~6min.

8. The method for preparing autoclaved aerated concrete (AAC) ultra-high performance extruded cement fiberboard according to claim 6, characterized in that, In step (3), the extruder vacuum is -0.06 to -0.09 MPa, the extrusion speed is 0.8 to 1.5 m / min, the screw speed is 18 to 28 r / min, and the die pressure is 1.0 to 1.4 MPa.

9. The method for preparing autoclaved aerated ultra-high performance extruded cement fiberboard according to claim 6, characterized in that, In steps (4) and (5), the pre-curing environment temperature is 20±5℃, the relative humidity is 60~70%, the pre-curing time is 2~4h, and the demolding strength threshold is ≥12MPa.

10. The method for preparing autoclaved aerated ultra-high performance extruded cement fiberboard according to claim 6, characterized in that, In step (6), the ambient temperature for natural curing is 20±5℃, the relative humidity is 60~70%, and the curing period is no less than 28 days.

Citation Information

Patent Citations

  • Extrusion-molded carbon mineralized fiber cement board and preparation method thereof

    CN120794553A